Improvement of Science Learning Outcomes With Problem Based Learning Method: Class Action Research Study - Desi Desi (International Journal of Educational Dynamics, 2019)
This research was conducted due to fifth grade studen’s low learning achievement at SD Negeri 10 Sapiran Bukittinggi. The aim of this research was to describe the improvement of the student’s learning achievement in Natural Scince by using Problem Based Learning (PBL) strategy in the fifth grade of SD Negeri 10 Sapiran Bukittinggi. This was a classroom action researchwhich applied qualitative and quantitative approaches.the resultof the research indicated that thestudent’slearning achievement improved from 78,01in the first cycle into 93,22 in the second cycle. Hence, the use of PBL strategy could improve the students learning achievement in Natural Science in the fifth grade of SD Negeri 10 Sapiran Bukittinggi.